INFLUENCER MARKETING AS EXPLOITATION OF CUSTOMERS FOR BUSINESS PERFORMANCE : Received: 27th October 2021; Revised: 20th January 2022, 01st March 2022, 07th March 2022; Accepted: 08th March 2022 - Ishola, Abdulfatai Idomi (MATTER: International Journal of Science and Technology, 2022)
Influencer marketing has become inherent for every business that wants to thrive, using social media as a marketing communication strategy. In Nigeria, entrepreneurship is fraught with many challenges which entrepreneurs are facing in the course of doing business. As a result of these challenges, stimulating customer interest is becoming of utmost importance. This study investigates influencer marketing as a marketing communication tool to encourage customer patronage. The research consists of customers that buy and patronized small and medium scale enterprises (SMEs) firms within Kwara State in Nigeria. The questionnaire was conveniently distributed among 300 participants, but 268 was used for the study. Regression analysis was used to survey the data collected. The findings revealed that influencer marketing has a positive significant impact on business performance. Further findings showed that social influence and e-WOM play an important role in stimulating customer interest, desire, willingness, and readiness to buy and patronize products or services. It was therefore recommended that influencer marketing should be explored by the entrepreneur due to its potential benefit and the consequence of its absence on the business performance.